THE PRESENCE OF RISK FACTORS FOR SUICIDAL BEHAVIOR AMONG MEDICAL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Youth suicide is currently one of the most pressing and pressing issues facing our society. The high suicide rate necessitates the early identification of risk factors for suicidal behavior for prevention.